2008
DOI: 10.1110/ps.033910.107
|View full text |Cite
|
Sign up to set email alerts
|

Cl–π interactions in protein–ligand complexes

Abstract: During systematic analysis of nonbonded contacts in protein-ligand complexes derived from crystal structures in the Protein Data Bank, Cl-p interactions have been found, not only in the well-documented serine proteases but also, to a lesser extent, in other proteins. From geometric analysis of such Cl-p interactions in the crystal structures, two distinct geometries were found: the ''edge-on'' approach of a Cl atom to a ring atom or C-C bond and the ''face-on'' approach toward the ring centroid with an average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
139
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 191 publications
(154 citation statements)
references
References 30 publications
13
139
0
2
Order By: Relevance
“…This is consistent with previous SAPT results on model R-X···benzene complexes [24,25] and with the results of Imai and coworkers [27], who used Morokuma decomposition and comparison of Hartree-Fock and MP2 results to investigate the origins of attraction in R-Cl···benzene complexes. SAPT dispersion components fall in the range between −3.35 kcal/mol and −4.29 kcal/mol, while the electrostatic term ranges from −1.05 kcal/mol and −1.86 kcal/mol.…”
Section: -70 +70supporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with previous SAPT results on model R-X···benzene complexes [24,25] and with the results of Imai and coworkers [27], who used Morokuma decomposition and comparison of Hartree-Fock and MP2 results to investigate the origins of attraction in R-Cl···benzene complexes. SAPT dispersion components fall in the range between −3.35 kcal/mol and −4.29 kcal/mol, while the electrostatic term ranges from −1.05 kcal/mol and −1.86 kcal/mol.…”
Section: -70 +70supporting
confidence: 92%
“…In recent protein database (PDB) survey studies seeking to identify halogen bonds existing in protein-ligand complexes, R-X···π interactions have been found to be one of the most common types of halogen bonding motifs [9,[26][27][28]. Examples of R-X···π interactions that contribute to the stabilization of protein-ligand complexes are given in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the geometries of the interactions, the q angle of the Cl atom relative to the plane of the ring was measured as shown in Figure 1A. Details of the searching procedure have been reported in previous articles [1,8].…”
Section: -P Interaction Search Of the Pdbmentioning
confidence: 99%
“…Kinbara et al reported that the para-chlorine substituent of the 1-(4-chlorophenyl)ethylammonium cation increases the positive charge of the meta-hydrogen atoms, effectively stabilizing the C-H•••π interaction [18]. In contrast, the chlorine atom of salt 9 did not show any short contacts (e.g., Cl•••Cl, Cl•••O, or Cl•••π interactions [22]). The same is true for the chlorine atom of salt 8 (see below).…”
Section: Molecular Packing Of Mαnp Salts (2): Stacking Of Sheet Strucmentioning
confidence: 99%